Risk Estimation of Breast Cancer - Elfigih, Seraj Omar B. (faculty of Basic Medical Science - Libyan International Medical University, 2018)
Breast cancer is cancer that develops from breast tissue and is the leading type of cancer in women. Several methods have been introduced to predict the risk of developing breast cancer which include but not limited to; single-nucleotide polymorphisms, mammographic density, and hormone measurements. single-nucleotide polymorphisms can be responsible for a large percentage of cancers in the population and it can be determined by the patients’ polygenic risk score which found that Women in the highest 1% of the polygenic risk score had a three-fold increased risk of developing breast cancer. Mammographic feature studies pointed out that women with 70% or more density was 4.64-fold at greater risk for developing breast cancer. Hormone measurement studies indicated that excess levels of hormones other than estradiol, free estradiol, progesterone and sex hormone binding globulin, such as testosterone and free testosterone were associated with an increased overall risk of breast cancer.
Breast cancer is cancer that develops from breast tissue. Signs of breast cancer may include a lump in the breast, a change in breast shape, dimpling of the skin, fluid coming from the nipple, or a red scaly patch of skin. 1 Outcomes for breast cancer vary depending on the cancer type, extent of disease, and person's age. Survival rates in the developed world are high, with between 80% and 90% of those in England and the United States alive for at least 5 years. In developing countries survival rates are poorer. Worldwide, breast cancer is the leading type of cancer in women, accounting for 25% of all cases. In 2012, it resulted in 1.68 million new cases and 522,000 deaths.2 Breast cancer is an increasing public health problem, as substantial advances have been made in the treatment of breast cancer, but the introduction of methods to predict women at elevated risk and prevent the disease has been less successful. The aim of this report is to summarize recent data on newer approaches to risk prediction, and available approaches to prevention